Carbon sequestration in tropical forests and water: a critical look at the basis for commonly used generalizations - Malmer, A.; Murdiyarso, Daniel; Bruijnzeel, L.A.; Ilstedt, Ulrik (2009)
Tree planting in the tropics is conducted for a number of reasons including carbon sequestration, but often competes with increasingly scarce water resources. The basics of forest and water relations are frequently said to be well understood but there is a pressing need to better understand and predict the hydrological effects of land-use and climate change in the complex and dynamic landscapes of the tropics. This will remain elusive without the empirical data required to feed hydrological process models. It is argued that the current state of knowledge is confused by too broad a use of the terms ‘forest’ and ‘(af)forestation’, as well as by a bias towards using data generated mostly outside the tropics and for nondegraded soil conditions. Definitions of forest, afforestation and reforestation as used in the climate change community and their application by land and water managers need to be reconciled.